2003
DOI: 10.1348/096317903769647229
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Emotional Labour Scale

Abstract: This paper describes the development and validation of the Emotional Labour Scale (ELS) as tested on samples of 296 and 238 respondents. The ELS is a 15‐item self‐report questionnaire that measures six facets of emotional display in the workplace, including the frequency, intensity and variety of emotional display, the duration of interaction, and surface and deep acting. Estimates of internal consistency for the subscales ranged from .74 to .91. Confirmatory factor analysis results provided support for the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
814
3
57

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 950 publications
(911 citation statements)
references
References 21 publications
37
814
3
57
Order By: Relevance
“…On the other hand, although deep acting also requires effort from the part of the individual it normally results in greater alignment between actual and displayed emotions; hence, in a reduction in the respective dissonance. These differences between deep and surface acting are critical as regards the ways in which they relate, or they are expected to relate, to outcomes of emotion work (e.g., Ashforth & Tomiuk, 2000;Brotheridge & Lee, 2003;Grandey, 2003;Hochschild, 1983;Morris & Feldman, 1996;Rafaeli & Sutton, 1987;Zapf, 2002).…”
Section: How It Relates To Emotional Exhaustion and Work Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, although deep acting also requires effort from the part of the individual it normally results in greater alignment between actual and displayed emotions; hence, in a reduction in the respective dissonance. These differences between deep and surface acting are critical as regards the ways in which they relate, or they are expected to relate, to outcomes of emotion work (e.g., Ashforth & Tomiuk, 2000;Brotheridge & Lee, 2003;Grandey, 2003;Hochschild, 1983;Morris & Feldman, 1996;Rafaeli & Sutton, 1987;Zapf, 2002).…”
Section: How It Relates To Emotional Exhaustion and Work Attitudesmentioning
confidence: 99%
“…These dimensions pertain to characteristics and demands of emotion work that are not encompassed by the disguise or modification of one's actual feelings, and include the frequency of emotional display, the intensity of displayed emotion, and the variety of displayed emotions (Brotheridge & Lee, 2003;Morris & Feldman, 1996). Surface and deep acting have been considered as primary dimensions of emotion work, whilst frequency, intensity and variety…”
Section: How It Relates To Emotional Exhaustion and Work Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found evidence of a link between emotional labour and emotional exhaustion ( e.g. Brotheridge and Lee 2003;Näring et al 2006;Zammuner and Lotto 2001). Such findings are in line with the more general idea that emotional job demands may lead to burnout (Maslach 1982).…”
mentioning
confidence: 99%
“…Globalement, la régulation de surface s'avère plus néfastes pour l'employé (Brotheridge & Lee, 2002;Mann, 1999;Schaubroek & Jones, 2000;Côté & Morgan, 2002;Brotheridge & Grandey, 2002;Grandey, 2003). Toutefois, la stratégie de profondeur n'exerce aucun effet ou sinon un effet bénéfique sur ces mêmes conséquences (Grandey, 2003;Brotheridge & Grandey, 2002;Brotheridge & Lee, 2003).…”
Section: Stratégies De Régulationunclassified